Expressive Timing or Thematic Transformation? Onset Displacement in Performances of Jazz Standard Melodies - Smither, Sean (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2025)
The rhythms of jazz standard melodies are inherently flexible prototypes that are brought to life by jazz musicians using a variety of expressive transformations. I argue that these transformations fall under two closely related categories. The first, expressive timing, involves displacements of onsets that are so small—usually in the order of milliseconds—that they do not constitute a change in metric-hierarchic position; they fall below the level of syntax. Conversely, thematic transformation often involves displacing notes to a different metric position. In this paper, I contend that expressive timing and thematic transformation represent interrelated improvisational processes that are coordinated in performances of jazz standards. I connect these techniques to recent work on jazz ontology and referents, arguing that the ambiguous relationships between these transformational categories is the result of the ontological flexibility of jazz tune melodies. I ultimately argue that both techniques become involved in an ongoing give-and-take as the improvisational process unfolds.